2016
DOI: 10.3171/2015.10.jns151036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of aneurysmal subarachnoid hemorrhage with intracerebral hematoma

Abstract: OBJECTIVE Intracerebral hematoma (ICH) with subarachnoid hemorrhage (SAH) indicates a unique feature of intracranial aneurysm rupture since the aneurysm is in the subarachnoid space and separated from the brain by pia mater. Broad consensus is lacking regarding the concept that ultra-early treatment improves outcome. The aim of this study is to determine the associative factors for ICH, ascertain the prognostic value of ICH, and investigate how the timing of treatment relates to the outcome of SAH with concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 27 publications
7
31
3
3
Order By: Relevance
“…Additionally, the occurrence of a cerebral vasospasm that greatly interrupts functional recovery is associated with the amount of hemorrhage in aSAH [25]. The presence of an ICH with aSAH is a well-known risk factor for a poor neurologic outcome [26]; although patients who showed a co-existing ICH were excluded to rule out this influence, the amount of hemorrhage itself was an independent predictor for dysphagia after stroke onset with ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the occurrence of a cerebral vasospasm that greatly interrupts functional recovery is associated with the amount of hemorrhage in aSAH [25]. The presence of an ICH with aSAH is a well-known risk factor for a poor neurologic outcome [26]; although patients who showed a co-existing ICH were excluded to rule out this influence, the amount of hemorrhage itself was an independent predictor for dysphagia after stroke onset with ICH.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain the lower rate of DCI in Fisher grade 4 versus grade 3 patients. Furthermore, due to the presence of an IPH, Fisher 4 patients may be in poorer clinical condition which masks clinical deterioration [66]. The Fisher scale lacks a separate grade for patients with both thick SAH and IVH, which the modified Fisher does have.…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of early definitive treatment remain controversial for patients with aSAH 50 , especially for those with poorgrade aSAH. One study showed early definitive treatment to be associated with less re-bleeding and a higher proportion of favorable outcomes 18 , while another did not 51 .…”
Section: Discussionmentioning
confidence: 99%